Business Information Systems Workshops : BIS 2016 International Workshops, Leipzig, Germany, July 6-8, 2016, Revised Papers - Abramowicz, Witold; Alt, Rainer; Franczyk, Bogdan (Springer, 2017)
This book constitutes revised papers from the six workshops held at the 19th International Conference on Business Information Systems, BIS 2016, held in Leipzig, Germany, in July 2016. The workshops included in this volume are: * The 8th Workshop on Applications of Knowledge-Based Technologies in Business - AKTB2016 accepted 7 papers from 14 submissions and features 1 invited talk. * The 7th Workshop on Business and IT Alignment - BITA 2016 selected 6 papers from 12 submissions. * The Workshop on Big Data and Business Analytics Ecosystems - DeBASE 2016 has 4 papers in this volume. * The First International Workshop on Intelligent Data Analysis in Integrated Social CRM - iCRM 2016 features 5 contributions. * The Second International Workshop on Digital Enterprise Engineering and Architecture - IDEA 2016 contributes 4 papers to this volume. * The First International Workshop on Integrative Analysis and Computation of Life Data for Smart Ecosystems - INCLuDE 2016 publishes 4 research papers. In addition, BIS hosted a Doctoral Consortium which was organized in a workshop formula. The best papers from this event are included in the book. In total, the workshops had 84 submissions of which 38 were accepted for publication.
Keywords: Business -- Data processing -- Congresses.; Management information systems -- Congresses.; Data mining -- Congresses.; elektronické knihy; electronic books